Early weight-bearing in operatively fixed ankle fractures: A systematic review - Black, J.D.J.; Bhavikatti, M.; Al-Hadithy, N.; Hakmi, A.; Kitson, J. (Foot (Edinburgh, Scotland), 2013)
Ankle fractures are among the most common lower limb fractures and they can cause significant detrimental effects on quality of life and work. The objective of the review was to evaluate if there is any advantage of early weight-bearing after open reduction and internal fixation of the ankle. Electronic databases, reference lists of included studies and relevant systematic reviews were searched for randomized and non-randomized controlled trials in adults comparing early and late weight-bearing after open reduction and internal fixation of the ankle. The search was inclusive up to February 2012. Nine studies comprising 555 subjects were included for review. There were significantly better outcomes for improved early dorsiflexion, time to full weight-bearing, early return to previous work and shorter hospital stay (patient<60 years of age) in the early weight-bearing group. The evidence base contained many methodological limitations and was generally poor, and so any conclusion drawn from the research must be done so with caution. The literature suggests that early weight-bearing may allow for quicker rehabilitation and earlier return to work. Future studies should focus on randomized controlled trials with narrow range of clinically useful outcome measures and consistent immobilization strategy between experimental groups.